Supporting Wajir communities to carry out participatory rangeland management - Tam, Kristen; Nganga, Irene; Flintan, Fiona (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Participatory Rangeland Management (PRM) builds the capacities of communities to better manage, govern and restore their lands. In 2023, as part of the International Livestock Research Institute's contribution to AICCRA in Kenya, local NGO Resource Conflict Institute (RECONCILE) worked with local government and community representatives to establish PRM for resident pastoralists in Arbajahan ward in Wajir county.